الجرائم الماسة بأمن وسلامة المستهلك في عملية تداول المواد الصيدلانية - مجدوب, نوال; لخضر, عيسى (Revue jurisprudence, 2018)
وفر المشرع الجزائري حماية قانونية للمستهلك في إطار عملية تسويق وتداول المواد الصيدلانية، وذلك من خلال قانون الصحة الجزائري والقانون رقم 09/03 المتعلق بحماية المستهلك وقمع الغش، بإعتبار أن المخاطر المنجرة عن عملية تداول المواد الصيدلانية بغض النظر عن كونها معيبة أو مغشوشة أو مقلدة كانت ومازالت في كل يوم تكشف عن وجه جديد، لاسيما مع بزوغ فجر المواد الصيدلانية المهندسة وراثيا والمواد الصيدلانية الجنيسة . لكن، ورغم سعي المشرع الجزائري الدؤوب لخلق بيئة قانونية تؤطر وتنظم عملية تداول المنتوجات الصيدلانية، إلا أن هذا لا ينفي وجود نقائص تشوب المنظومة القانونية المنوط بها تنظيم عملية تداول المواد الصيدلانية، مما يتطلب معه التشدد في أحكام المسائلة الجنائية ضد كل متدخل مخالف لقواعد تسويق المواد الصيدلانية بدءا من مرحلة الإنتاج إلى غاية الوصول إلى مرحلة الوضع للبيع . ا لكلمات المفتاحية : المستهلك، المواد الصيدلانية، التداول، الجرائم . abstract: Algerian legislator has provided legal protection for the consumer in the context of the process of marketing of pharmaceuticals and through the health law and consumption Algerian law no 09/03 of consumer protection, considering that the risks involved in pharmaceuticals , regardless of whether they are defective or adulterated and was stilled very day reveals a new face , especially prong dawn pharmaceuticals genetically engineered and generic pharmaceuticals. despite the quest Algerian legislator hard to create a legal environment that affect and regulate the marketing of pharmaceutical products process but this does not negate the existence of some short comings that mar the legal system , which requires him to militancy in the provisions of the criminal accountability against each intervention in contrary to the rules of marketing of pharmaceuticals from production stage until access to stage the situation of the sale. key words: consumer , pharmaceutical , marketing , legal protection.